Nanoscale Surface Modification for Enhanced Biosensing: A Journey Toward Better Glucose Monitoring - Zhang, Guigen (Springer, 2015)
This book gives a comprehensive overview of electrochemical-based biosensors and their crucial components. Practical examples are given throughout the text to illustrate how the performance of electrochemical-based biosensors can be improved by nanoscale surface modification and how an optimal design can be achieved. All essential aspects of biosensors are considered, including electrode functionalization, efficiency of the mass transport of reactive species, and long term durability and functionality of the sensor.